Brainstem auditory evoked potentials in children with autism spectrum disorder - Mariana Keiko Kamita; Liliane Aparecida Fagundes Silva; Fernanda Cristina Leite Magliaro; Rebeca Yuko Couto Kawai; Fernanda Dreux Miranda Fernandes; Carla Gentile Matas (Brazilian Society of Pediatrics, 2020)
Objectives: This study aimed to analyze the neural encoding of verbal and nonverbal stimuli in individuals with autism spectrum disorder using brainstem auditory evoked potentials. Methodology: Thirty individuals between 7 and 12 years of age and of both genders participated in this study. Fifteen were diagnosed with autism spectrum disorder, and 15 had typical development. All subjects had normal hearing and no other impairments. An electrophysiological hearing assessment was performed using brainstem auditory evoked potentials with click and speech stimuli. Results: In the brainstem auditory evoked potentials with click stimuli, the mean wave I latency was longer for the right ear in both groups, and interpeak intervals III-V were greater for the individuals with autism spectrum disorder. For brainstem auditory evoked potentials with speech stimuli, wave V latency was shorter in individuals with autism spectrum disorder. Conclusion: These data suggest that individuals with autism spectrum disorder may have a dysfunction of the central auditory nervous system for nonverbal stimuli and faster neural encoding of the initial part of the verbal stimulus, suggesting hypersensitivity to complex sounds such as speech. Resumo: Objetivos: Este estudo visou analisar a codificação neural de estímulos verbais e não verbais em indivíduos com transtorno do espectro do autismo com o uso de potenciais evocados auditivos de tronco encefálico. Metodologia: Participaram 30 indivíduos entre sete e 12 anos e de ambos os sexos; 15 foram diagnosticados com transtorno do espectro do autismo e 15 apresentaram desenvolvimento típico. Todos os indivíduos apresentaram audição normal e nenhuma outra alteração. Foi feita uma avaliação eletrofisiológica da audição com o uso dos potenciais evocados auditivos de tronco encefálico com estímulos de clique e fala. Resultados: Nos potenciais evocados auditivos de tronco encefálico com estímulos de clique, a média do valor de latência da onda I foi maior para o ouvido direito nos dois grupos e os intervalos interpicos III‐V foram maiores para os indivíduos com transtorno do espectro do autismo. Para os potenciais evocados auditivos de tronco encefálico com estímulos de fala, a latência da onda V foi menor nos indivíduos com transtorno do espectro do autismo. Conclusão: Nossos dados sugerem que os indivíduos com transtorno do espectro do autismo podem ter uma disfunção do sistema nervoso auditivo central para estímulos não verbais e codificação neural mais rápida da parte inicial dos estímulos verbais, o que sugere hipersensibilidade a sons complexos, como a fala.